ANALISIS TEKNIKAL SAHAM MENGGUNAKAN INDIKATOR TRUE STRENGTH INDEX (TSI) - , NABILA KENCANA; , Prof. Dr. Sri Haryatmi Kartiko, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Technical analysis using a graph as method, itâs used to predicting price movement of its stocks so that we know when we have to buy or sell our stocks in a way gaining maximum profits. There are a lot of indicators that can be used at stock technical analysis. True Strength Index (TSI) indicator in a technical momentum indicator that helps traders determine overbought and oversold conditions of a security by incorporating the short-term purchasing momentum of the market with the lagging benefits of moving average. Generally is a 25-day Exponential Momentum (EMA) is applied to the difference between two share prices, and then a 13-day EMA is applied to the result, making the indicator more sensitive to prevailing market condotions. After the data is smoothed, value of -20 dan +20 used to identify levels where a security is overbought or oversold. Itâll proof TSI based on EMA is the best than TSI based on SMA and WMA. TSI indicator is a variation of the Relative Strength Index (RSI).